Challenges, mitigation strategies and perspectives in development of Li metal anode. Issue 6 (10th October 2020) - Wang, Zaisheng; Yu, Jiawen; Rao, Mumin; Jin, Xiaojin; Huld, Frederik; Xu, Zhenming; Li, Yong; Lou, Fengliu; Ye, Daiqi; Qiu, Yongcai
Abstract: Lithium (Li) metal anode has been considered as the most promising anode for rechargeable batteries with high energy density owing to its extraordinarily high theoretical specific capacity (3860 mAh g −1 ) and the lowest negative electrochemical potential (–3.040 V vs. the standard hydrogen electrode). However, the practical applications of the Li metal anode are hampered by several obstacles, such as irrepressible dendritic Li growth and limited Coulombic efficiency (CE) during Li plating/stripping. To improve the application scope of Li metal batteries, it is imperative to develop advanced strategies to figure out these issues. In this Review, we first clarify the fundamental factors that affect the dendrite growth and CE of the Li metal anode. Subsequently, based on the previous theoretical understanding and analysis, recently proposed strategies to suppress dendrite growth and accommodating volume change have been reviewed. In addition, advanced characterization techniques for Li metal anode are included. Finally, a general conclusion and a perspective for the coming development of Li metal anode in practical applications are provided. Abstract : The paper reviews the fundamental factors that affecting the dendrite growth and Coulombic efficiency, the proposed strategies of suppressing the dendrite growth and accommodating volume change, and advanced characterization techniques of Li metal anode. A general conclusion and a perspective of Li metal anode in practical applications also are discussed.